Pengaruh Kompetensi Sumber Daya Manusia, Pengetahuan Akuntansi, Tingkat Pendidikan, Motivasi Kerja, dan Pengalaman Kerja Terhadap Pembuatan Laporan Keuangan UMKM di Kecamatan Tambakromo Kabupaten Pati - Annisa Fitrotun Nadhiroh; Putri, Eskasari (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
This study aims to measure the influence of human resource competence, accounting knowledge, education level, work motivation, and work experience on the preparation of financial reports in Micro, Small, and Medium Enterprises (MSMEs) in Tambakromo District, Pati Regency. Research data were collected by distributing questionnaires to 101 respondents who were MSME actors in the area. Data analysis was carried out using multiple linear regression methods to test the relationship between independent variables and dependent variables. The results of the study showed that human resource competence had a significant negative effect on the preparation of financial reports, while accounting knowledge, work motivation, and work experience had a significant positive effect. On the other hand, education level did not show a significant effect on the preparation of financial reports.